PROFESIONALITAS GURU MATA PELAJARAN BAHASA INDONESIA DI TINGKAT MI/SD (TUNTUTAN, FAKTA DAN SOLUSI) - Lilis Sumaryanti (Universitas Muhammadiyah Ponorogo, 2018)
The main tasks of teachers include bridging students to be able to adapt to various challenges such as the urges experienced and developed within the individual itself. The challenges faced by the world of education include producing quality human resources so as to overcome the demands of a competitive nature. Teacher professional competencies include pedagogical, personality, social, and professional competence. A teacher is a figure of a leader who deserves to be imitated in building and shaping the character of his students so that later useful for religion, nation and country. Three cultures that are considered important in an effort to improve the professionalism of teachers is the culture of reading, writing and researching. Reality, until now Indonesian people including teachers has not made reading, writing and researching as a culture in everyday life. Teacher homeroom teacher at MI/SD level must master enough subjects and can use the model and the right method of learning, one of them on the lessons of Indonesia language. Professional skills of teachers at MI/SD level can be achieved by holding PTK (Research Action Class), play an active interactive in the development of science in accordance with the cluster of teaching through seminars and workshops, but also must master the competence of ICT (information and communication technology) as a means of self-development with the use of tools in the form of media.